Thermal Performance Of A Triple-Pass Solar Dryer - Wong, Hui Qin (2021)
Dehydration of agricultural products is an ancient skill to extend the shelf life of crops and reduce post-harvest losses. Owing to the global food security problem, severe post-harvest losses, disadvantages of open sun drying and environmental issues arised from industrial drying, solar drying technologies has become point of interest of researchers to improve the thermal performances of the solar drying system from different aspect. Existing solar dryer are usually design for specific crops type and facing multiple limitations such as inefficient conversion of solar radiation, low collector temperature, long drying time and intermittent drying caused by unpredictable weather. Hence, the objectives of this research work is to develop a solar drying system with optimized thermal performance. By considering the climatic profile of Malaysia and gathering the recommended parameters from the literature, an indirect solar dryer with triple-pass solar air collector and heat storage unit was designed and fabricated. The thermal performance of the triple-pass solar collector was studied and optimized from the aspect of arrangement of porous media, type of heat storage materials and air circulation mode. The solar collector achieved the maximum instantaneous efficiency of 84.7% ± 9.0% with cement and iron mesh as heat storage materials, loosely packed arrangement of porous media and forced convection of mass flow rate of 0.01252 kg/s. The solar dryer was tested with mass flow rate of 0.00834 kg/s, 0.01252 kg/s and 0.01669 kg/s, and the highest drying chamber temperature achieved were 53.5°C, 65.2°C and 56.3°C, respectively. Tea leaves were dried by using the solar dryer and open sun drying methods on a same experiment day.